The Effect of SISKEUDES Implementation, Village Apparatus Training, and Internal Control System on The Quality of Village Financial Reports - Darwanis, Darwanis (UNIB Press, 2023)
This study aims to determine the effect of SISKEUDES implementation, village apparatus training, and internal control system on the quality of village financial reports in Simeulue Regency, Aceh Province. The population included 138 villages in Simeulue Regency with a census sample of 138 villages. The respondents comprised three people in each village, with a total of 414 respondents. This study performed multiple linear regression using the SPSS (Statistical Package For Social Science) program for data analysis. The results showed that the implementation of SISKEUDES, technical training, and internal control systems show a positive and significant effect on the quality of village financial reports in Simeulue Regency. The implementation of SISKEUDES has positive effects on the quality of village financial reports in Simeulue Regency. The technical training and the internal control system also showed positive effects on the quality of village financial reports in Simeulue Regency. The implication of the finding is expected to be the basis for policymakers to implement SISKEUDES, technical training for village officials, and the implementation of an internal control system. This also becomes a practical guideline for villages to manage their finances.